(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Amongthe tens of thousands of Indians who ventured to Britain in the 250 years priorto 1857, there were more than thirty diplomatic and political missions fromIndian rulers or would-be rulers to London. These Indian agents soughtadvancement or financial benefits for their Indian patrons. These envoysnegotiated, lobbied, and purchased political support from British politiciansand East India Company Directors, as well as seeking to influence the Britishpublic through speeches and published books, articles, and newspaper columns.This paper examines two such diplomatic missions, both from the Mughal Emperorto the British monarch and Parliament. The first, by al-Din(1766–69), sought the Briths King’s military aid in restoring the MughalEmperor to power. The second, by Raja Ram Mohan Roy (1831–33), soughtenhancement of the Emperor’s pension. These two missions are set in the contextof the other diplomatic and political missions, and also in the otherasymmetrical exchanges between Indians and Britons in both India and Britain inthe pre-1857 period.